Progress and prospects in stem cell therapy and drug discovery - Zhou Qi (Acta Pharmacologica Sinica, 2016)
Qi ZHOU* State Key Laboratory of Reproductive Biology, Institute of Zoology, Chinese Academy of Sciences, Beijing 100101, China * To whom correspondence should be addressed. E-mail zhouqi@ioz.ac.cn